Optimal parameters and location for diffusion tensor imaging in the diagnosis of carpal tunnel syndrome: a meta-analysis. Issue 12 (December 2018) - Liu, C.; Li, H.W.; Wang, L.; Zhu, L.; Jiang, X.F.; Yang, M.J.; Li, B.; Zhang, C.; Yang, H.F.; Xu, X.X.
Abstract : Aim: To assess the diagnostic value of the apparent diffusion coefficient (ADC) and fractional anisotropy (FA) of diffusion tensor imaging (DTI) at several anatomical locations in patients with carpal tunnel syndrome (CTS) to explore the optimal parameters and measurement location. Materials and methods: A search was conducted using the PubMed, EBSCO, Ovid, Web of Science, and Cochrane databases to identify articles relevant to this study published before September 2017. Studies were selected and included according to strict eligibility criteria. Mean differences (MD) and 95% confidence intervals (CIs) were used to compare FA and ADC values between CTS patients and healthy subjects. Potential publication bias was investigated. Results: Eleven studies involving 349 CTS wrists and 278 controls were selected for the meta-analysis. A notable MD: was found for lowered FA at the level of the pisiform bone for CTS versus controls (MD: –0.11, 95% confidence interval [CI]: –1.14 to –0.07, z= 5.83, p< 0.001). A higher ADC was found at the pisiform bone and hamate bone levels for CTS versus controls (P: MD: 0.15, 95% CI: 0.10 to 0.20, z= 5.98, p< 0.001, H: MD: 0.15; 95% CI: 0.09 to 0.21, z= 4.67, p< 0.001). Conclusions: The meta-analysis demonstrated a significant FA reduction and ADC increase in CTS patients. This result supports the use of DTI parameters in differentiating CTS patients from health subjects. The anatomical site for FA at the pisiform and ADC at the pisiform and hamate levels were more accessible than other sites for the diagnosis of CTS patients.